Disincentive effects of evaluation - Raphael Boleslavsky; Bruce Ian Carlin; Christopher Cotton (Queen's University, Department of Economics, 2019)
In a model of project design, evaluation, and selection, we explore how the incentives to improve the design of projects depend on the availability of funding and the process of evaluation. We show that project designers (researchers or NGOs) prefer to subject their projects to less-rigorous evaluations than donors or funding agencies would prefer, ex post. We also find that increases in both funding availability and the informativeness of evaluations tend to decrease investments in project quality. By implication, increased availability of funding or more-informative evaluations can lead to the implementation of fewer high-value projects.
Keywords: D83; H43; O22; 330; Game theory; Impact evaluation; Pilot studies; Funding allocation